Perancangan Antena Mikrostrip Rectangular Crab Patch sebagai Antena Eksternal Penerima Sinyal 4G Frekuensi 2,3 GHz - Suryani, Mary Alysia; Diwyacitta, Branita Adwitiya; Rafsyam, Yenniwarti (Politeknik Negeri Jakarta, 2025)
Wireless 4G communication has become an essential part of supporting daily digital services such as internet browsing, video streaming, and low-latency applications. However, 4G signal reception often faces degradation in various locations, particularly in remote areas or inside buildings with structural barriers. One effective solution to enhance signal reception is the use of a microstrip antenna, which offers advantages such as a simple design, compact size, and low manufacturing cost. This study presents the design of a rectangular crab patch microstrip antenna for 4G signal reception operating at a frequency of 2.3 GHz. The antenna was designed with a patch size of 15.5 mm, an inter-element spacing of 62.5 mm, a dielectric constant (εr) of 4.3, and a substrate thickness (h) of 1.6 mm. The simulation results show that the antenna achieved an S₁₁ of –46.26 dB, a VSWR of 1.009, and a gain of 3.53 dB. Overall, the antenna meets the expected performance criteria and is suitable for effective 4G signal reception.